Assistência Social de Brumadinho-MG: impactos e desafios após o rompimento da Barragem em Córrego do Feijão - Wallace Cristiano da Silva (2024)
The tragedy/crime in Córrego do Feijão, in Brumadinho, resulted in a collapse in Public Policy assistance, as has rarely been seen in Brazil, generating profound transformations in the dynamics and structure of Social Assistance in the municipality. This study, based on bibliographical and documentary research, uses the content analysis methodology to examine the article "Assistência Social de Brumadinho-MG: impacts and challenges after the collapse of the Dam in Córrego do Feijão", in order to reflect on the changes and impacts on Brumadinho's Municipal Social Assistance Policy, highlighting the main challenges to implementing an effective response to the consequences of the tragedy/crime of the Dam in Córrego do Feijão.